Analisis Laporan Keuangan PT Bank Panin Dubai Syariah TBK (PNBS) - Angeline Angeline; Angelica Lee; Caroline Caroline; Fransiska Fransiska; Viony Viony (GEMILANG: Jurnal Manajemen dan Akuntansi, 2024)
This report examines the development of the Islamic banking industry in Indonesia, with a focus on PT. Bank Panin Dubai Syariah Tbk (PNBS). Since its establishment in 2009, PNBS has experienced rapid growth and played a significant role in the Islamic banking sector. The research aims to understand how PNBS channels funds through various financing instruments such as mudharabah, musyarakah, ijarah, and murabahah, as well as determine the percentage contribution of each instrument to the total financing. Additionally, this study classifies the instruments based on Maqashid Sharia, distinguishing between pseudo-Islamic, sharia-compliant, and sharia-based. The results show that PNBS adheres to Sharia principles in its financing activities. Furthermore, mudharabah and musyarakah financing instruments make a significant contribution to the total financing, while ijarah and murabahah financing also play essential roles. The classification of instruments indicates that PNBS leans more towards sharia-compliant and sharia-based rather than pseudo-Islamic. This research provides a deep understanding of Islamic bank financing strategies and their alignment with Sharia principles, assisting banks in planning more effective strategies and promoting transparency and public trust in the Islamic banking industry.